G471 Somatic mosaicism in X-linked PDHA1 gene – a cause of developmental delay and epilepsy. (7th April 2014) - Kutty, JS; Crushell, E; King, M; Hughes, JAF
Abstract : Background: Pyruvate dehydrogenase complex (PDHc) deficiency is an inborn error of metabolism that occurs most commonly due to mutations in the X-linked E1α subunit gene (PDHA1). PDHc plays a critical role in carbohydrate metabolism and energy production. Deficiency typically presents with lactic acidosis and a progressive neurodegenerative disorder. Method: We report a 2 year old male, born to non-consanguineous parents, who presented with feeding difficulties and central hypotonia in the neonatal period. Initial investigation showed a raised CSF lactate and MRI brain scan showed mild dilatation of lateral and 3rd ventricles and patchy white matter changes. He developed infantile spasms at 5 months and was noted to be developmentally delayed. Investigations showed elevated plasma and CSF lactate and alanine levels, abnormal urine organic acids and a significant rise in lactate post glucose load suggesting a defect of energy metabolism. Whilst PDHc activity in skin fibroblasts was below normal it was not felt to be indicative of true PDHc deficiency. SURF1 mutation and POLG1 analysis were negative. Fatty acid oxidation studies on skin fibroblasts were normal. Respiratory chain enzymology on muscle was normal prompting further studies of the PDHA1 gene. Results: Mutation analysis of PDHA1 in blood and fibroblasts revealed a missense mutation in Exon 4, c.364G >A, G122S. He was noted to be heterozygous for this mutation in both cDNA and genomic DNA. As this child had normal karyotype and microarray, the most likely explanation is that he has somatic mosaicism, which is sporadic and carries a much lower recurrence risk than if his mother was a carrier. Conclusion: This case highlights the importance of pursuing a molecular genetics cause for disease when the biochemistry is equivocal to allow for accurate diagnosis and appropriate genetic counselling.